Gingival recession in mandibular incisors and symphysis morphology-a retrospective cohort study - Mazurova, Katarina; Kopp, Jean-Baptiste; Renkema, Anne Marie; Pandis, Nikolaos; Katsaros, Christos; Fudalej, Piotr S (European journal of orthodontics, 2018)
Objective: To evaluate if the morphology of the mandibular symphysis is associated with the development of gingival recession. Materials and methods: A cohort of 177 patients was followed longitudinally for up to 5 years post-treatment. Based on the width of the symphysis, participants were divided into three groups: narrow (n = 57); average (n = 63), and wide symphysis (n = 57). Morphology of the symphysis and inclination of incisors were measured on lateral cephalometric radiographs before treatment (Ts), at the end of treatment (T0) and 5 years after treatment (T5). Gingival recession and the change of clinical crown heights in mandibular incisors were measured on plaster models made at TS, T0, and T5. Results: From TS to T5 the change in inclination was comparable in the narrow, average, and wide groups. At T5, gingival labial recession was present in 19.3 per cent of patients with narrow symphysis, 20.6 per cent with average symphysis, and 14 per cent of patients with wide symphysis. The difference was not significant. The mean change of clinical crown height was <1 mm (TS - T5). The regression model showed some evidence that incisor inclination at Ts might have been associated with the change of mean clinical crown height (-2.51, 95% CI: -4.6 to -0.4, P = 0.02). The logistic regression model demonstrated that H1 (Height 1) might be associated with the development of gingival recession (OR = 0.75, 95% CI: 0.58 to 0.96, P = 0.03). Conclusion: Within the limitations of this study, there is no evidence that the overall morphology of the mandibular symphysis is associated with gingival recession development.
Keywords: ústup dásní; Mandible; řezáky; Humans; Longitudinal Studies; kefalometrie; dítě; kohortové studie; Child; Cephalometry; Female; Orthodontics, Corrective; Gingival Recession; lidé; ortodoncie korekční; Incisor; Cohort Studies; ženské pohlaví; longitudinální studie; Male; Retrospective Studies; Adolescent; retrospektivní studie; mandibula; mužské pohlaví; mladiství